Management of Clinically Insignificant Residual Fragments following Shock Wave Lithotripsy - Elisa Cicerello; Franco Merlo; Luigi Maccatrozzo (Advances in Urology)
Clinically insignificant residual fragments (CIRFs) are small fragments (less than 5 mm) that are present in upper urinary tract at the time of regular post-SWL followup. The term is controversial because they may remain silent and asymptomatic or become a risk factor for stone growth and recurrence, leading to symptomatic events, and need further urologic treatment. Although a stone-free state is the desired outcome of surgical treatment of urolithiasis, the authors believe that the presence of noninfected, nonobstructive, asymptomatic residual fragments can be managed metabolically in order to prevent stone growth and recurrence. Further urologic intervention is warranted if clinical indications for stone removal are present.